معاني ألفاظ اليسر والعسر وما يشتق منهما في القرآن الكريم - Wahyudin, Dedih; Husna Hamzah, Tina Asmaul (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2020)
This study aims to determine the lexical meaning, contextual meaning, and educational implications of the words "yusr" and "'usr" and their derivation in the Qur’an. This research is based on a framework using semantics, namely isytirāk (one word that has many meanings) as a tool to find out the meanings that have implications for the science of education. The research method used is the semantic analysis study by leading to the analysis of the meaning of the word with thematic methods, And the data collection techniques in this study use literature study techniques. After the researcher analyzed the words "yusr" and "’usr" and their derivatives in the Qur'an, it can be concluded that the word "yusr" means easy, to ease, simplify, good deeds, invisible, little/small, gentle, heaven and solution. The word "usr" means distress, difficulty, inability to pay debts, problem difficulty, doomsday, partner differences, ugliness, and hell. The words "yusr" and "'usr" have educational implications that are seen in each of their meanings.